Characteristics of Rural Architectural Housing Typologies in Doukkala area, Morocco - El aoud, Youssef (Journal for Geography, 2025)
Doukkala, located in central Morocco, features diverse rural architecture shaped by nine tribes according to local resources and traditions. This article explores the transition from traditional to modern housing, highlighting differences in form, construction methods, materials, and functions, as well as challenges faced by rural dwellings. It also examines state efforts to preserve and valorize traditional housing as cultural heritage. The study applies a descriptive and historical approach, combining field research, scientific literature, and terrain observation using ArcGIS and satellite imagery to analyze rural housing typologies in the Doukkala region.